2010
DOI: 10.1111/j.1420-9101.2010.02147.x
|View full text |Cite
|
Sign up to set email alerts
|

Incipient allochronic speciation in the pine processionary moth (Thaumetopoea pityocampa, Lepidoptera, Notodontidae)

Abstract: A plausible case of allochronic differentiation, where barrier to gene flow is primarily attributable to a phenological shift, was recently discovered in Portugal for the pine processionary moth Thaumetopoea pityocampa. Previous results suggested that the observed ‘summer population’ (SP) originated from the sympatric winter population (WP). Our objectives were to finely analyse these patterns and test their stability in time, through field monitoring and genetic analyses of larvae and adults across different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 49 publications
4
97
0
Order By: Relevance
“…We determine the biogeographic origin of populations at the sympatric sites is likely to have come from within the Coast Range, not from the Sierra Nevada. This case, along with other recent work on temporal isolation [1, 911, 13, 55, 56] demonstrates that temporal isolation may occur more frequently than previously thought and warrants further research into the underlying mechanism of this process of reproductive isolation.…”
Section: Discussionsupporting
confidence: 53%
“…We determine the biogeographic origin of populations at the sympatric sites is likely to have come from within the Coast Range, not from the Sierra Nevada. This case, along with other recent work on temporal isolation [1, 911, 13, 55, 56] demonstrates that temporal isolation may occur more frequently than previously thought and warrants further research into the underlying mechanism of this process of reproductive isolation.…”
Section: Discussionsupporting
confidence: 53%
“…Santos et al (2011a) obtained data supporting the hypothesis that the SP has relatively recently evolved from the sympatric ancestral WP. Theoretically, the differences observed between the SP and the typical populations could have resulted either from local genetic adaptation, phenotypic plasticity, or drift following a founder effect in Leiria forest.…”
Section: Discussionmentioning
confidence: 82%
“…The later was chosen due to its location, ca. 150 km south from Leiria, at the same elevation and longitude, presenting a phenology similar to the Leiria WP, while previous data showed that genetic differentiation between them is very limited (Santos et al 2011a). …”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Molecular ecology studies with highly reliable and statistically powerful molecular markers as microsatellites can help us to identify patterns of dispersion/migration determining scales of genetic divergence (Torriani et al, 2010), population differentiation through geographic discontinuities (Abila et al, 2008), the degree of population differentiation related to host plants (Carletto et al, 2009), and the process of sympatric speciation (Santos et al, 2011). Microsatellite markers developed for D. saccharalis in this study can be applied in further population genetic studies to address ecological and evolutionary questions and also to improve our ability to manage populations of this species according to local integrated pest management practices.…”
Section: Resultsmentioning
confidence: 99%